FINITE STATE AUTOMATA DAN LOGIKA FUZZY DALAM PEMILIHAN PAKET PELAMINAN DI KOTA BATAM - Koko Handoko; Alvendo Wahyu Aranski (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
Marriage is something that is highly desirable for every potential partner in life. Marriage is considered a sacred activity so it needs to be well planned and mature. The growing development of a business in Batam city makes this business mushrooming because it is definitely needed by every couple who will get married. The availability of a wedding package helps each couple to choose an existing package, both in terms of price, type of tent to be used, number of clothes, and wedding photographer services. In this study, researchers conducted a determination of the problem in the form of a wedding package selection, looking for literature in accordance with the problems in the form of books and journals, analysis with fuzzy logic with the Mamdani method to complete the exact calculations so that prospective brides who will choose the aids package can choose the package that in accordance with the wishes and budget provided. The use of fuzzy logic and the Mamdani method will be assisted by Finite State Automata in making the rule design of fuzzy logic. Output targets achieved in the form of analysis of the determination of the package in the form of fuzzy logic calculations, system design from the analysis stage, retrieval of real data from each aisle in the city of Batam, and the target in the first year in the form of a determination package relevant to every wedding in the city of Batam.